Design, Implementation, and Results of a Workshop for Students Failing University Physics in Chemical Engineering - Escobar-Moreno, Fabiola (2023)
Aim. To design a psycho-pedagogical intervention (workshop) based on didactic planning, articulated to the 5 E model. It is an intervention different from what has been done historically in the Physics Academy of a Mexican public university. Methodology. This research project had a descriptive and ethnographic approach. Various instruments were used for data collection, including a diagnostic test of classical mechanics for engineering with content validity, the ADHD Rating Scale test, the Big Five personality factors theory, resumes, and direct interviews. These data were analyzed with a methodological triangulation. Results. The intervention had 100% approval since empirical evidence shows that didactic planning is useful and stimulating. This planning is based on the 5 E model, specifically for the aforementioned workshop, with activities with high pedagogical content and the intensive use of learning and knowledge technologies. Also, the traits and study habits of participants were characterized. Conclusions. According to the ADHD Rating Scale, presumably, the student body does not report ADHD; inattention markers stand out from this instrument, and as a result of the five-factor theory, there are no indications of the responsibility trait. Thus, the psycho-pedagogical intervention favors strengthening study habits in the lagging student body.